Characterization of insect-specific Culex flavivirus (Flaviviridae) nucleotide sequences in mosquitoes from urban parks in São Paulo, Brazil - Thaís de Moura Coletti; Camila Malta Romano; Paulo Roberto Urbinatti; Renildo Souza Teixeira; Leila Weiss de Almeida Pedrosa; Marcello Schiavo Nardi; Delsio Natal; Antônio Charlys da Costa; Jaqueline Goes de Jesus; Ingra Morales Claro; Ester Cerdeira Sabino; Steven S. Witkin; et al. (Revista da Sociedade Brasileira de Medicina Tropical, 2022)
ABSTRACT Background: Despite their worldwide occurrence, the distribution and role of insect-specific flaviviruses (ISFs) remain unclear. Methods: We evaluated the presence of ISFs in mosquitoes collected in São Paulo, Brazil, using reverse transcription and semi-nested polymerase chain reaction (PCR). Some of the positive samples were subjected to nanopore sequencing. Results: Twelve mosquito pools (2.8%) tested positive for flavivirus infection. Nanopore sequencing was successfully performed on six samples. Phylogenetic analysis grouped these sequences into genotype 2 of Culex flavivirus (CxFV). Conclusions: The identification of CxFV genotype 2 at new locations in São Paulo highlights the importance of understanding the role of ISFs in mosquito vector competence.